Drug use according to risk classification and associated factors among pregnant women: results from NISAMI cohort (Research, Society and Development, 2020)
This study aimed to investigate the factors associated with drug use in pregnancy by risk categories in pregnant women from Santo Antônio de Jesus, Bahia. It is a cross-sectional cohort study with 1,091 pregnant women attended in primary health care between 2012 and 2014. Drug use during pregnancy was classified according to the FDA’s pregnancy risk classification. Prevalence ratios and respective 95% confidence intervals were adjusted by Poisson regression with robust error variance. The prevalence of drug use was more pronounced in risk categories A, B, C, D, and X, respectively. The use of safe medication was associated with education, number of prenatal consultations, and health problems after data adjustment. Age greater than 24 years, onset of prenatal care during the first trimester, and have any health problem were factors associated with the use of risk medication. Quality prenatal care is important to ensure the safe and conscious use of drugs. Furthermore, investments in continuing vocational education that promote rational antenatal drug use are needed.